"CHANGES IN THE EPIDEMILOGY OF MEASLES DUE TO MASS-VACCINATION IN IRAN (1961-1971) " - A. Manteghi (Tehran University of Medical Sciences, 1972)
Measles is one of the viral and extremely contagious and acute diseases of childhood affecting almost all children. Prior to the discovery of the measles vaccine, the mortality from this disease was one of the highest child mortality figures, especially in the developing countries, with the death rate ranging over 5 to 10% of the infected? Before the vaccination program I was launched in the country, the number of cases of this disease varied between 150.000 to 500,000 during non epidemic and epidemic years, with the mortality more than 10 or 15 per cent the cases in rural and mountainous localities. The available statistics show that the highest figure of measles patient in Iran belongs to the 1-7 years age-group and the highest of its mortality belongs to the age between 1-2 years. In view of the high morbidity and mortality rates of this disease, and thanks to the quick growth under way in public health maters, gradually the significance of this grave problem was more felt. Thus, to control the disease, the ministry of health decided, in 19.6566, to carry out a study program with the help of the Institute of Public Health Research and, with the desired result on hand from the experimental vaccines, to launch a mass vaccination campaign against measles. Consequently, the mass vaccination program was started from 1967, with priority being given to rura1 area and mountainous localities. From 1970, with the cooperation of the ministry of health and Razi Institute the measles vaccine was produced within the country, and, by the end of 1971 the number of vaccinated children was about 3,517,547 which constitutes almost 37% of the susceptible population. The out come has been I an obvious decline in the prevalence and incidence of this disease and an outstanding change in its epidemiological trend. Thus, in the event that the rate of susceptible population coverage by this vaccine (a single shoot or which gives permanent or at least, a long immunity) should reach 70-80% along with other health measures and systemic surveillance, the disease will entirely come under control.